Pengetahuan Ibu Tentang Tumbuh Kembang Terhadap Perkembangan Anak Usia Prasekolah Di Lingkungan Jempong Timur Wilayah Kerja Puskesmas Karang Pule - Indah Wasilah (Jurnal PRIMA, 2021)
Introduction: The level of fracture in RSUD DR. R Soedjono Selong increased in 2018 totaled 424 cases from the previous year 327 cases. Pain is one of the typical complaints experienced by fracture patients. The treatment of fracture patients is focused on controlling pain (pain), reducing joint and bone damage, and improving or maintaining function and quality of life. One of the treatment of fracture patients is non-pharmacological therapy, namely instrumental music therapyObjective: . The purpose of this study was to determine the effectiveness of instrumental music therapy to change the scale of pain in fracture patients in the Operating Room of RSUD Dr. R. Soedjono Selong.Method: The research design used was one group pre-test-post test design. Sampling using purposive sampling as many as 26 people. Observation method is used to observe the pain that appears in respondents using the Bourbonais pain scale checklist sheet to determine the intensity of pain. Analysis of data using the Wilcoxon Signed Rank Test.Results: The results showed that the majority of fracture pain levels before (pre-test) were treated with instrumental music therapy, namely moderate pain as many as 21 people (80.8%), and most of the level of fracture pain after (post-test) were given instrumental music therapy treatment, namely mild pain as many as 22 people (84.6%)Conclusion: The conclusion of this study is the effectiveness of instrumental music therapy to change the pain scale in fracture patients.